2012
DOI: 10.1021/np300250m
|View full text |Cite
|
Sign up to set email alerts
|

Dual Inhibition of γ-Oryzanol on Cellular Melanogenesis: Inhibition of Tyrosinase Activity and Reduction of Melanogenic Gene Expression by a Protein Kinase A-Dependent Mechanism

Abstract: The in vitro effects on melanogenesis of γ-oryzanol (1), a rice bran-derived phytosterol, were investigated. The melanin content in B16F1 cells was significantly and dose-dependently reduced (-13% and -28% at 3 and 30 μM, respectively). Tyrosinase enzyme activity was inhibited by 1 both in a cell-free assay and when analyzed based on the measurement of cellular tyrosinase activity. Transcriptome analysis was performed to investigate the biological pathways altered by 1, and it was found that gene expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Interestingly, RR shows synergistic effects in comparison that of each resveratrol or rice alone (Baek et al, 2013;Baek et al, 2014). Several reports show that resveratrol decreases the expression of tyrosinase (Franco et al, 2012;Zheng et al, 2012;Bae et al, 2013;Park and Boo, 2013;Park et al, 2014), and Jun et al reported that gamma-oryzanol from rice extract dually inhibited cellular melanogenesis, too (Jun et al, 2012). Because each of resveratrol and rice had anti-melanogenic effects, we expected that RR would produce synergistic antimelanogenic effects and thus have some advantages over treatment with rice or resveratrol alone.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, RR shows synergistic effects in comparison that of each resveratrol or rice alone (Baek et al, 2013;Baek et al, 2014). Several reports show that resveratrol decreases the expression of tyrosinase (Franco et al, 2012;Zheng et al, 2012;Bae et al, 2013;Park and Boo, 2013;Park et al, 2014), and Jun et al reported that gamma-oryzanol from rice extract dually inhibited cellular melanogenesis, too (Jun et al, 2012). Because each of resveratrol and rice had anti-melanogenic effects, we expected that RR would produce synergistic antimelanogenic effects and thus have some advantages over treatment with rice or resveratrol alone.…”
Section: Discussionmentioning
confidence: 97%
“…Previous published literature showed that phenolic constituents can act as inhibitors of these enzymes [39], thus suggesting that multiple compounds in the phytocomplex of G. diversifolia may be the responsible for the observed activity. Regarding the tyrosinase activity, literature data indicate that the phytosterol fraction indicated as oryzanol has significant inhibitory properties on this enzyme [30].…”
Section: Discussionmentioning
confidence: 99%
“…Related to the tyrosinase activity, in this case the presence of high levels of phytosterols can also be related to the observed effect. A previous paper showed a significant effect for γ-oryzanol in cellular melanogenesis owing to its inhibition of tyrosinase enzyme activity and reduction of MITF and target genes in the PKA-dependent pathway [30].…”
Section: In Vitro Bioassaysmentioning
confidence: 98%
“…In a study on rats with colon cancer, it was found that γ-oryzanol has the capability to improve immunity by increasing the activity of both natural killer and macrophages cells . It was also found that γ-oryzanol is able to reduce melanin concentration by decreasing its synthesis in melanoma cells (Jun et al, 2012). In addition, γ-oryzanol *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%